Resistance profile of improved cassava germplasm to cassava mosaic disease in Nigeria - Egesi, Chiedozie N.; Ogbe, F.O.; Akoroda, M.O.; Ilona, Paul; Dixon, A. (Springer, 2007)
Cassava mosaic disease (CMD) caused by a group of begomoviruses and transmitted by whitefly vector is a serious disease in all the cassava-growing areas of Africa. Field evaluation with replication was conducted in 2003 and 2004 in three agroecologies in Nigeria to study the response of 40 cassava genotypes to CMD and to investigate genotype• environment (GE) interactions on their reactions to CMD, using the rank-sum classification and site regression analysis model. The 40 genotypes were separated into resistant (n= 17), moderately resistant (n= 6), moderately susceptible (n= 2) and susceptible (n= 15) groups. Environments, genotypes and GE interactions were all highly significant (P< 0.0001) for the virus disease contributing 9.5%, 71.36% and 19.14%, respectively to total variation. More than 40% of the genotypes were identified as resistant to the disease. Genotypes TMS 980581, TMS 993073, TMS 974763, TMS M980040, TMS 980505, TMS 970211, TMS 974769, TMS 992123, TMS M980068 and TMS 970162 were shown to have high resistance to CMD. The study also identified Umudike, in south-east Nigeria, as having high disease severity and the most appropriate site for CMD resistance screening of genotypes. Most of the genotypes exhibited stable resistance to CMD. The implication that the availability of these resistant genotypes as identified in this study could be a source of CMD resistance for further breeding is discussed.